2016
DOI: 10.1007/s10853-016-9859-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxide dispersion-strengthened steel PM2000 after dynamic plastic deformation: nanostructure and annealing behaviour

Abstract: The microstructure, texture and mechanical properties have been studied in PM2000 compressed via dynamic plastic deformation to a strain of 2.1. It is found that dynamic plastic deformation results in a duplex h111i ? h100i fibre texture and refines the initial microstructure by nanoscale lamellae, which substantially increases the strength of the material, but decreases its thermal stability. In the as-deformed microstructure, the stored energy density is found to be higher in h111i-oriented regions than in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
2
6
1
Order By: Relevance
“…Calculations based on the EBSD data show that the stored energy is significantly reduced during coarsening (see Figure 12), and that the reduction rate is higher in the h111i regions, for which the initial stored energy was greater than that for the h100i regions. This observation is in agreement with our recent results obtained on PM2000 annealed after DPD [4] and with findings obtained on commercial purity aluminum annealed after heavy rolling, [24] where more pronounced recovery was observed in high-energy texture bands compared to Figure 12), it is clear that the different reduction in the stored energy for the different regions is predominantly caused by differences in the loss of LABs.…”
Section: B Recoverysupporting
confidence: 93%
See 1 more Smart Citation
“…Calculations based on the EBSD data show that the stored energy is significantly reduced during coarsening (see Figure 12), and that the reduction rate is higher in the h111i regions, for which the initial stored energy was greater than that for the h100i regions. This observation is in agreement with our recent results obtained on PM2000 annealed after DPD [4] and with findings obtained on commercial purity aluminum annealed after heavy rolling, [24] where more pronounced recovery was observed in high-energy texture bands compared to Figure 12), it is clear that the different reduction in the stored energy for the different regions is predominantly caused by differences in the loss of LABs.…”
Section: B Recoverysupporting
confidence: 93%
“…For body-centered cubic (bcc) iron-based systems, the deformation texture after compression is dominated by h100i and h111i fiber texture components aligned with the compression axis (CA), and it is generally found that the h100i component weakens during recrystallization, whereas the h111i fiber texture strengthens significantly. [1][2][3][4] In a previous study [3] on a modified ferritic/martensitic 9Cr-1Mo steel where samples were deformed to a strain of 0.5 either by quasistatic compression (QSC) or by dynamic plastic deformation (DPD), [5,6] it has been found that DPD resulted in a stronger h111i + h100i fiber texture and in faster recrystallization than QSC. The faster recrystallization was attributed to a finer boundary spacing and, therefore, a higher energy stored during DPD as compared to QSC.…”
Section: Introductionmentioning
confidence: 99%
“…During compression the texture changes, as crystal orientations rotate towards the stable components of the compression texture. Such stable components in bcc materials are known to be fibers with 111 and 100 parallel to the compression axis [28][29][30][31]. It should be noted that for the present sample, which was compressed along the ND of the rolled material, the  fiber of the rolling texture is coincident with the 111 fiber of the compression texture.…”
Section: Effects Of Compression On Microstructure and Texturementioning
confidence: 59%
“…The difference between the obtained and macroscopic yield stress is likely to be caused by material heterogeneity; the yield strength of PM2000 is grain size dependent 53 and the volume of material affected by the nanoindentation is significant relative to the grain size. Tensile data reported in other studies of bulk specimens of PM2000 steels 53 54 provide strain hardening exponents between 0.04 and 0.17.…”
Section: Resultsmentioning
confidence: 75%